The aminotransferase Aat initiates 3-phenyllactic acid biosynthesis in Pediococcus acidilactici - Wenger, Alexander; Bär, Cornelia; Portmann, Reto; Schmidt, Remo S.; Eugster, Elisabeth; Weisskopf, Laure; Irmler, Stefan (Frontiers in Microbiology, 2023)
The function of the aminotransferase Aat (GenBank Protein WP_159211138) from Pediococcus acidilactici FAM 18098 was studied in vivo. For this purpose, the gene was replaced with an erythromycin resistance gene using the temperature-sensitive Escherichia coli-Pediococcus shuttle plasmid pSET4T_Δaat. Genome sequencing of the mutant strain confirmed the aat knockout. Subsequently, the differences between the metabolism of the knockout and of the wild-type strain were investigated by determining the free amino acids and organic acids in culture supernatants. It was found that the knockout mutant no longer synthesized 3-phenyllactic acid (PLA) and 4-hydroxyphenyllactic acid (HPLA). Additionally, the mutant strain no longer catabolized phenylalanine. To study the transfer of the amino group of phenylalanine, the wild-type strain was incubated with [15N] phenylalanine. Mass spectrometry showed that during fermentation, [15N] alanine was formed, indicating that pyruvic acid is the amino group acceptor. The present study shows that Aat plays a crucial role in PLA/HPLA biosynthesis and pyruvic acid is an amino acceptor in transamination reactions in P. acidilactici.